A Clinical Audit of Pap Smear Test for Screening of Cervical Cancer - Tamrakar, SR; Chawla, CD (Nepal Journal of Obstetrics and Gynaecology, 2014)
Aims: Cervical cancer is a major cause of morbidity and mortality in gynecology clients. It accounts for the most common cancer in women. A Papanicolaou (Pap) smear test (cervical cytology screening) is one of the best tests to screen for cervical cancer in its premalignant stage. The objective of this study is to find out the prevalence of abnormal Pap smear results and to determine the contributing factors for it. Methods: The out patient clinic register was reviewed. Out-patients clinic register from 1 Jan 2008 to 31 Dec 2011showed that a total of 25511 gynecology clients were seen. In these four years duration, a total of 1506 Pap smear samples were taken which accounted for 5.9% of the total gynecology clients. The samples were collected only after proper counseling and consent from the clients who visited the clinic for various gynecology complaints. Assumed predictors of abnormal Pap smear results were examined through inferential way (Chi square test) using Software SPSS version 13.0 for Windows. Results: The preliminary analysis showed the mean age was 37.57 ± 10.72 years (ranging from 18 to 81 years). Most of them were of Newar caste (28.7%), with 3 children (37.6%) and from Kavre District (66%). Most of them (343 clients) were of age group 30 – 34 years whereas 15.8, 10.8, 3.1 and 10.0 % (clients were of 40 – 44, 45 – 49, 50 – 54 and 55 above respectively. A total of 1062 samples were normal whereas 379 samples were suggestive of inflammatory and 39 samples were inadequate for evaluation. We had 22 samples suspicious for malignancy and/or low grade squamous intraepithelial lesion (LSIL) and 4 frank malignant cases. This accounted for 1.7% of total Pap smear samples. These cases were scheduled for colposcopic guided biopsies and histologic evaluations. There was significant difference between the age groups and Pap smear results (p=0.003) and parity with Pap smear results (p=0.000, highly significant). But there was no significant difference between caste and Pap smear results (p=0.166). Conclusions: There is no doubt that Pap test is one of the best and easiest tests to screen for precancerous and cancerous cervical lesions. In order to have a high yield it has to be combined with other alternative tests like HPV testing and/or visual inspection with acetic acid (VIA) or Lugol’s Iodine (VILI). Besides its use as screening tool, we can also evaluate for chronic cervicitis, sexually transmitted infection (STI), pelvic inflammatory disease (PID)and genital prolapse (if any) in same setting. Thus the community people will have broader benefits from the screening program. DOI: http://www.dx.doi.org/10.3126/njog.v7i2.11137 Nepal Journal of Obstetrics and Gynaecology / Vol 7 / No. 2 / Issue 14 / July-Dec, 2012 / 21-24